Kabbalah and creativity: from ancient mystical texts to contemporary artistic practice - Brown, Rosslyn (2025)
This thesis explores the role(s) and meaning(s) of material images, the visual arts, and artistic creators in Jewish Kabbalah. My main contention is that human artistic creativity can be both theurgic and messianic – that is, capable of contributing towards tikkun olam. In Part 1, I examine what the central Kabbalistic texts and figures suggest about the status and function of human artistic creativity and material images in the mystical tradition. I consider notions such as imago Dei, imitatio Dei, mitzvah, tikkun olam, tikkun ha-nefesh, tikkun atzmi, kavvanah, the imagination, the Second Commandment, and beauty, as well as Kabbalistic ilanot and ilan-amulets. In Part 2, I explore how four contemporary artists – Daniel Shorkend, Beth Ames Swartz, Susan Leshnoff, and Mirta Kupferminc – understand the relationship between Kabbalah and creativity themselves. Through a combination of interviews and correspondences with these artists, as well as formal element analyses of their artworks, I seek to answer the question: how do ancient Kabbalistic beliefs continue to influence artistic practice in the present? Through the close readings offered in Part 1, and the case studies in Part 2, I ultimately demonstrate that artistic creativity, material images, and the visual arts can be deemed significant aspects of the Kabbalistic worldview(s) because of their redemptive capability.